Indian agriculture under climate change: The competing effect of temperature and rainfall anomalies - Johannes Gallé; Anja Katzenberger (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
The latest generation of global climate models robustly projects that the summer monsoon rainfall in India will significantly increase in the 21st century due to global warming and that rainfall anomalies will occur more often. This raises the question of the impact of these changes on the agricultural yield. Based on annual district data for the years 1966-2014, we estimate the relationship between weather indices (amount of seasonal rainfall, number of wet days, average temperature) and the most widely grown kharif crops, including rice, in a flexible non-parametric way. We use this relationship in order to predict district-specific crop yield based on the climate projections of eight different climate models of the Coupled Model Intercomparison Project - phase 6 (CMIP6) under two global warming scenarios (Shared Socioeconomic Pathways SSP1-2.6 & SSP5-8.5) for the years 2021-2100 (short-term, mid-term, long-term). We find that the loss in rice yield by the end of the 21st century lies on average between 3 - 22% depending on the underlying emission scenario. Potential gains due to increasing rainfall are more than offset by the negative impacts of increasing temperature. Adaptation efforts in the worst case scenario (SSP5-8.5) would need to cut the negative impacts of temperature by 50% in order to reach the outcome of the sustainable scenario (SSP1-2.6). – – Die aktuellste Generation globaler Klimamodelle projiziert, dass der Niederschlag während des Sommermonsuns in Indien im 21. Jahrhundert aufgrund der globalen Erwärmung erheblich zunehmen wird. Dies wirft die Frage auf, wie sich diese Veränderungen auf die landwirtschaftlichen Erträge auswirken werden. Auf Basis von Daten auf Distriktebene für die Jahre 1966-2014 schätzen wir den empirischen Zusammenhang zwischen Wetterindizes (Saisonaler Niederschlag, Anzahl der Regentage, Durchschnittstemperatur) und den am häufigsten angebauten Feldfrüchten, inklusive Reis, in einer flexiblen und nicht-parametrischen Herangehensweise. Wir nutzen den geschätzten Zusammenhang, um distrikt-spezifische Ernteerträge auf Grundlage von Klimaprojektionen von acht evaluierten Klimamodellen des Coupled Model Intercomparison Project - Phase 6 (CMIP6) unter zwei globalen Emissionsszenarien (Shared Socioeconomic Pathways SSP1-2.6 & SSP5-8.5) für die Jahre 2021-2100 (kurzfristig, mittelfristig, langfristig) vorherzusagen. Wir zeigen, dass die Verluste bei den Reiserträgen bis zum Ende des 21. Jahrhunderts je nach zugrunde liegendem Emissionsszenario im Durchschnitt zwischen 3 % und 22 % liegen. Potenzielle Gewinne durch zunehmende Niederschläge werden durch die negativen Auswirkungen des Temperaturanstiegs mehr als ausgeglichen. Anpassungsbemühungen im ungünstigsten Szenario (SSP5-8.5) müssten die negativen Auswirkungen der Temperatur um 50 % reduzieren, um das Ergebnis des nachhaltigen Szenarios (SSP1-2.6) zu erreichen.
Keywords: Q10; Q54; O53; 330; Climate change; monsoon; agriculture; India